Theologization of Greek Terms and Concepts in the Septuagint and New Testament - Mickiewicz, Franciszek (Verbum Vitae, 2021)
Hellenistic literature, having great achievements in the fields of philosophy, drama, and poetry, did not know the theological concepts and issues which underlie the texts contained in the Hebrew Bible. So when the creators of the Septuagint, and then also the authors of the New Testament, used the Greek language to convey God’s inspired truths to the world, they were forced to give secular terms a new theological meaning, frequently choosing neutral words for this purpose, not burdened with negative associations. With their translation work, they built a kind of bridge between Hellenic and Jewish cultures. On the one hand, the Septuagint allowed Jews reading the Bible in Greek to remain connected not only with the religious heritage of their fathers, but also with the cultural values that were closely related to that language and its world. In turn, for the Greeks, who after some time began to appreciate this work and gained knowledge of its content, it opened vast horizons of new religious and spiritual values, which until then were completely alien to them. The work of the authors of the Septuagint was continued and developed by the authors of the New Testament, which added to their theological output many new religious and moral values arising from the teaching of Jesus Christ. That way they contributed considerably to the development of the Koinē Greek and significantly transformed the spiritual life of the people speaking the language.